Development of a Multi-Item Inventory Model by Considering Perishable and Return of Goods in a Hospital Pharmacy - Roland Y.H. Silitonga; Ivena Jane Budiyono; Christine C. Bautista (The Indonesian Institute of Science and Technology Research, 2022)
In determining an inventory's quantity, some factors need to be considered. The factors to be considered in the pharmaceutical industry are the fluctuating demand factor (diseases are unpredictable) and the perishable factors. The purpose of this paper is to propose a probabilistic inventory model by considering perishable and return of goods. Compared to the previous models, the developed model has lower inventory costs when compared to the model not considering the return of goods and higher inventory costs when compared to the model that considers deterministic demand patterns. The sensitivity analysis was done to see the behavior of the total cost, component costs, and time to order. The parameters to be changed for the sensitivity test were a fraction of good condition goods, holding costs per unit per period, and ordering cost per unit per period. The analysis showed that total cost, based on joint order, is sensitive to the fraction of good condition products. In general, the model was perceived as able to describe the behavior of the model components.